Turbulence characteristics of the flexible circular cylinder agitator - Dol, S.S. (MDPI AG, 2021)
A flexible protruding surface was employed as the flow disturbance to promote turbulence at the area of interest. An ultrasonic velocity profiler, UVP technique, was used to study the mean and fluctuating flow properties in the near wake of the rigid and flexible protruding surface in a water tunnel. The polymer based, ethylene-vinyl acetate (EVA) with an aspect ratio of AR = 10, 12, 14, 16 was used as the flexible circular cylinder, and submerged in a flow at Re = 4000, 6000 and 8000. The motion of the cylinder altered the fluid flow significantly. As a means to quantify turbulence, the wakes regions and production terms were analyzed. In general, the flexible cylinders show better capability in augmenting the turbulence than the rigid cylinder. The results show that the turbulence production term generated by the flexible cylinder is higher than that of rigid cylinder. The localized maximum shear production values have increased significantly from 131, 203 and 94 against their rigid counterparts of AR = 16 at the Re = 4000, 6000 and 8000, respectively. The performance of turbulence enhancement depends heavily on the motion of the cylinder. The findings suggest that the turbulence enhancement was due to the oscillation of the flexible cylinder. The results have concluded that the flexible cylinder is a better turbulence generator than the rigid cylinder, thus improving the mixing of fluid through augmented turbulent flow. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.